(untitled) (Eurasian Journal of Research, Development and Innovation, 2023)
First of all, this article contains detailed information about the history of the emergence of cryptocurrency and blockchain technology today, its advantages and the prospects of its application in the fields. Key word: Blockchain technology, block chain, bitcoin, cryptocurrency, digital money, ethereum platform, Abstract: First of all, this article provides detailed information about the history, advantages and prospects of application of today’s cryptocurrency and blockchain technology in the fields. took place.